Activin Receptor Ligand Blocking and Cancer Have Distinct Effects on Protein and Redox Homeostasis in Skeletal Muscle and Liver - Jaakko Hentilä; Tuuli A. Nissinen; Ayhan Korkmaz; Sanna Lensu; Mika Silvennoinen; Arja Pasternack; Olli Ritvos; Mustafa Atalay; Juha J. Hulmi; Juha J. Hulmi (Frontiers in Physiology, 2019)
Muscle wasting in cancer cachexia can be alleviated by blocking activin receptor type 2 (ACVR2) ligands through changes in protein synthesis/degradation. These changes in cellular and protein metabolism may alter protein homeostasis. First, we elucidated the acute (1–2 days) and 2-week effects of blocking ACVR2 ligands by soluble activin receptor 2B (sACVR2B-Fc) on unfolded protein response (UPR), heat shock proteins (HSPs) and redox balance in a healthy mouse skeletal muscle. Second, we examined UPR, autophagy and redox balance with or without sACVR2B-Fc administration in muscle and liver of C26 tumor-bearing mice. The indicators of UPR and HSPs were not altered 1–2 days after a single sACVR2B-Fc administration in healthy muscles, but protein carbonyls increased (p < 0.05). Two weeks of sACVR2B-Fc administration increased muscle size, which was accompanied by increased UPR markers: GRP78 (p < 0.05), phosphorylated eIF2α (p < 0.01) and HSP47 (p < 0.01). Additionally, protein carbonyls and reduced form of glutathione increased (GSH) (p < 0.05). On the other hand, C26 cancer cachexia manifested decreased UPR markers (p-eIF2α, HSP47, p-JNK; p < 0.05) and antioxidant GSH (p < 0.001) in muscle, whereas the ratio of oxidized to reduced glutathione increased (GSSG/GSH; p < 0.001). Administration of sACVR2B-Fc prevented the decline in GSH and increased some of the UPR indicators in tumor-bearing mice. Additionally, autophagy markers LC3II/I (p < 0.05), Beclin-1 (p < 0.01), and P62 (p < 0.05) increased in the skeletal muscle of tumor-bearing mice. Finally, indicators of UPR, PERK, p-eIF2α and GRP78, increased (p < 0.05), whereas ATF4 was strongly decreased (p < 0.01) in the liver of tumor-bearing mice while sACVR2B-Fc had no effect. Muscle GSH and many of the altered UPR indicators correlated with tumor mass, fat mass and body mass loss. In conclusion, experimental cancer cachexia is accompanied by distinct and tissue-specific changes in proteostasis. Muscle hypertrophy induced by blocking ACVR2B ligands may be accompanied by the induction of UPR and increased protein carbonyls but blocking ACVR2B ligands may upregulate antioxidant protection.